CINTA, HARGA DIRI, DAN SIKAP TOKOH: SEBUAH KAJIAN PSIKOLOGI SASTRA (Love, Self-Esteem, and Attitude of Characters: A Study of Literature Psychology) - Purwati Anggraini; Bawon Wiji Dia Prasasti; Haris Supratno (Kandai, 2021)
Love and self-esteem are part of human needs as a form of self-existence. Attempts to reach and maintain love and self-esteem are reflected in the character's attitude. This study aims to describe the love needs and self-esteem needs of characters and how the characters behave in making it happen. The needs and behavior of characters in making it happen are closely related to literary psychology, so this study chooses literary psychology as its approach. This research used qualitative methods and was based on Abraham Maslow's theory. The data source was in the form of the novel Lengking Burung Kasuari by Nunuk Y. Kusmiana published by PT Gramedia Pustaka Utama in 2017. The data of this research were quotations from story units. The data collection techniques of this research were (a) reading the object of study, (b) identifying the data according to the research objectives, and (c) classifying the data. While the data analysis techniques were as follows, (a) rechecking the data in accordance with the problem formulation, (b) describing the data, (c) interpreting the data, (d) drawing conclusions. The results of the research can be stated as follows. First, the need for love includes feelings of longing for, playing, and caring for friends. Second, forms of need for self-esteem include broad insight, promotion, and responsibility. Third, the character tries to realize the need for love, the need for price self as a form of self-existence.Cinta dan harga diri merupakan bagian dari kebutuhan manusia sebagai salah satu wujud eksistensi diri. Upaya untuk menggapai dan mempertahankan cinta dan harga diri tecermin dalam sikap tokoh. Penelitian ini bertujuan untuk mendeskripsikan kebutuhan rasa cinta dan kebutuhan harga diri tokoh serta bagaimana perilaku tokoh dalam mewujudkannya. Kebutuhan dan perilaku tokoh dalam mewujudkannya terkait erat dengan psikologi sastra sehingga kajian ini memilih psikologi sastra sebagai pendekatannya. Penelitian ini menggunakan metode kualitatif dan dilandaskan pada teori Abraham Maslow. Sumber data berupa novel Lengking Burung Kasuari Karya Nunuk Y. Kusmiana yang diterbitkan oleh PT Gramedia Pustaka Utama tahun 2017. Data penelitian ini adalah kutipan satuan cerita. Teknik pengumpulan data penelitian ini adalah (a) membaca objek kajian, (b) mengidentifikasi data sesuai tujuan penelitian, dan (c) mengelompokan data. Di samping itu, teknik analisis data sebagai berikut: (a) mengecek kembali data yang sesuai dengan rumusan masalah; (b) mendeskripsikan data; (c) menginterpretasikan data; dan (d) menarik simpulan. Hasil penelitian dapat dikemukakan sebagai berikut. Pertama, kebutuhan rasa cinta meliputi perasaan rindu, bermain, dan peduli pada teman. Kedua, bentuk kebutuhan harga diri meliputi wawasan luas, naik pangkat, dan tanggung jawab. Ketiga, tokoh berupaya mewujudkan kebutuhan rasa cinta, kebutuhan harga diri sebagai wujud eksistensi diri.